2015
DOI: 10.1186/s12890-015-0106-z
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of a nicotine-free e-cigarette compared to a traditional cigarette in smokers and non-smokers

Abstract: BackgroundA few studies have assessed the short-term effects of low-dose nicotine e-cigarettes, while data about nicotine-free e-cigarettes (NF e-cigarettes) are scanty. Concerns have been expressed about the use of NF e-cigarettes, because of the high concentrations of propylene glycol and other compounds in the e-cigarette vapor.MethodsThis laboratory-based study was aimed to compare the effects of ad libitum use of a NF e-cigarette or and a traditional cigarette for 5 min in healthy adult smokers (n = 10) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 18 publications
2
62
0
10
Order By: Relevance
“…Laboratory studies find modest increases in nicotine biomarkers after vaping. 169,195,197,203,206,209211,215,222,223,232,233,239,246,248,264,271,284,300 Vaping has no or minimal impact on other physiologic measures (i.e., exhaled carbon monoxide, complete blood count, body weight), 142,202,203,230,237,239,242,257,265,272,274,276,282,285,292,303 with improvements in outcomes seen for smokers switching to ENDS, such as reduced blood pressure, improved lung function, and improved disease symptoms (i.e., asthma and chronic obstructive pulmonary disease). 214,230,273,287 Some studies have examined cardiovascular measures associated with vaping, 195,197,209,222,223,226,232,246,248,257,273,300,301 with the majority finding an increase in heart rate, 195,223,232,246,248,300 but three finding no change after use.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Laboratory studies find modest increases in nicotine biomarkers after vaping. 169,195,197,203,206,209211,215,222,223,232,233,239,246,248,264,271,284,300 Vaping has no or minimal impact on other physiologic measures (i.e., exhaled carbon monoxide, complete blood count, body weight), 142,202,203,230,237,239,242,257,265,272,274,276,282,285,292,303 with improvements in outcomes seen for smokers switching to ENDS, such as reduced blood pressure, improved lung function, and improved disease symptoms (i.e., asthma and chronic obstructive pulmonary disease). 214,230,273,287 Some studies have examined cardiovascular measures associated with vaping, 195,197,209,222,223,226,232,246,248,257,273,300,301 with the majority finding an increase in heart rate, 195,223,232,246,248,300 but three finding no change after use.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…While some of the studies found that e cigarette users experience increased airway resistance along with compromise in pulmonary function upon exposure to e cigarette vapor, 5,6 others reported that short term use of e cigarettes have no significant changes in lung function. 7,8 Further, two studies reported immediate reduction in exhaled nitric oxide similar to what is seen in tobacco smoking. 5,6 Another study found increase in inflammatory signalling molecules upon inhalation, in resemblance to what is seen in tobacco smoking.…”
Section: Cas E R Ep Ortmentioning
confidence: 95%
“…Ferrari et al (2015) discovered that in a group of 10 smokers and 10 non-smokers, 5 min of ad libitum use of a nicotine-free EC decreased the FEV1 value and the forced expiratory flow after 25% of the air in the lungs has been expelled (FEF25 value). This indicates that ECs can impair lung volume as well as the force lungs can generate, unrelated to nicotine.…”
Section: Effects Of Ecs On Pulmonary Functionmentioning
confidence: 99%
“…These effects were, however, more pronounced in the 10 smokers. Among the smokers, there was also a decreased peak (highest) expiratory flow (PEF value) when air was being expelled from the lungs (Ferrari et al 2015). Walele et al (2016) found no change in pulmonary function (including in values such as the FEV1) for flavoured or unflavoured liquid or varying nicotine concentrations when 24 smokers took 10 puffs from the EC device four times per day for 4 d. Again, these different results may be due to different puffing regimes or the use of different liquids or devices that may affect lung function differently.…”
Section: Effects Of Ecs On Pulmonary Functionmentioning
confidence: 99%